2005
DOI: 10.1258/0022215053419952
|View full text |Cite
|
Sign up to set email alerts
|

Parapharyngeal metastasis from papillary thyroid carcinoma: a case diagnosed by thyroglobulin measurement in peroral fine-needle aspiration of a cystic metastatic lymph node

Abstract: We report a case of a parapharyngeal cystic metastatic lymph node arising from papillary thyroid carcinoma (PTC). Parapharyngeal metastases arising from PTC are rare and correct diagnosis of the parapharyngeal mass before surgery is difficult. In this case, the diagnosis of a parapharyngeal mass was made pre-operatively by thyroglobulin measurement in peroral fine-needle aspiration with negative cytology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…Desuter et al [6] reported that only 0.43% (3/696) of thyroid papillary carcinomas had parapharyngeal node metastasis. During the last two decades, looking at only cases with histologically definite diagnosis by surgery, only 39 reported cases were found in the literature (Tables I and II) [6][7][8][9][10][11][12][13][14][15]. Therefore, we reviewed the literature of those 39 cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Desuter et al [6] reported that only 0.43% (3/696) of thyroid papillary carcinomas had parapharyngeal node metastasis. During the last two decades, looking at only cases with histologically definite diagnosis by surgery, only 39 reported cases were found in the literature (Tables I and II) [6][7][8][9][10][11][12][13][14][15]. Therefore, we reviewed the literature of those 39 cases.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of node metastasis usually occurs in the internal jugular and recurrent laryngeal chain on the side of the lesion [4,5], so metastasis to the retropharyngeal lymph nodes (RPLN) or parapharyngeal lymph nodes (PPLN) is very rare. Only 39 cases (limited to the cases with histologically definite diagnosis by surgery) have been reported during the last two decades within our literature review (Tables I and II) [6][7][8][9][10][11][12][13][14][15]. Meanwhile, it was reported that there were two lymphatic pathways that connected with a retropharyngeal metastasis from thyroid carcinomas, one is retrograde from jugular chain lymphatics, and the other is direct through the superior thyroid pole by way of the posterior lymphatic trunks, which are reported to be present in 20% of the cases [16].…”
Section: Introductionmentioning
confidence: 99%
“…Totally, two relatively large numbers of DTC cases with parapharyngeal metastases have been described, suggesting that the incidence rate of parapharyngeal metastasis is extremely low (Desuter et al 2004). Parapharyngeal mass is often nonspecific or asymptomatic when the tumor does not exceed 3.0 cm in size (Tomoda et al 2005). Frequently, patients complain of a mass in the neck or oropharynx that causes dysphagia.…”
Section: Parapharyngeal Metastasismentioning
confidence: 99%
“…Based on several reports investigating isolated cervical cystic masses related to papillary thyroid cancer, preoperative tissue sampling through fine needle aspiration (FNA) may aid in the differential diagnosis of cervical masses. [1,2] However, mere microscopic evaluation of fine-needle aspirates might not be sufficient for adequate diagnosis since they are commonly false negative. [3] Instead, thyroglobulin measurements in the specimen have been proven helpful for accurate diagnosis of cystic lesions as thyroid metastases.…”
Section: Discussionmentioning
confidence: 99%